Peculiarities of task-based method in teaching the professional English language - Viktoria V. Mironenko (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
The article is dedicated to the analysis of the application of the task-based method, which for a rather long period of time has been used for teaching the professional English language, with the aim of defining to what extent students use the material learned previously, in real situations.On the grounds of analysis of theoretical sources and pedagogical practices, the author offers a direction for searching the most efficient approaches and ways of solving the question of developing the problematic active basis for teaching the professional English language. The main stages of the lesson using the task-based method are examined and analyzed. Particular attention is paid to the advantages and disadvantages of this method. As a result of the research, it was indicated that the task- based method promotes the development of communication skills in pairs and groups, the ability of all participants to argue and debate in the learning process.